Linking Climate and Demography to Predict Population Dynamics and Persistence Under Global Change - Jennifer L. Williams; Amy L. Angert; Aldo Compagnoni; Ali Campbell; Megan L. DeMarche; Margaret E. K. Evans; Joshua C. Fowler; Edgar J. González; Amy M. Iler; Jenna A. Loesberg; Allison M. Louthan; Alexandra B. Martin; et al. (Ecology Letters, 2025)
Predicting the effects of climate change on plant and animal populations is an urgent challenge for understanding the fate of biodiversity under global change. At the surface, quantifying how climate drives the vital rates that underlie population dynamics appears simple, yet many decisions are required to connect climate to demographic data. Competing approaches have emerged in the literature with little consensus around best practices. Here we provide a practical guide for how to best link vital rates to climate for the purposes of inference and projection of population dynamics. We first describe the sources of demographic and climate data underlying population models. We then focus on best practices to model the relationships between vital rates and climate, highlighting what we can learn from mechanistic and phenomenological models. Finally, we discuss the challenges of prediction and forecasting in the face of uncertainty about climate‐demographic relationships as well as future climate. We conclude by suggesting ways forward to build this field of research into one that makes robust forecasts of population persistence, with opportunities for synthesis across species.

Diversity–stability relationships across organism groups and ecosystem types become decoupled across spatial scales - Nathan I. Wisnoski; Riley Andrade; Max C. N. Castorani; Christopher P. Catano; Aldo Compagnoni; Thomas Lamy; Nina K. Lany; Luca Marazzi; Sydne Record; Annie C. Smith; Christopher M. Swan; Jonathan D. Tonkin; et al. (Ecology, 2023)
The relationship between biodiversity and stability, or its inverse, temporal variability, is multidimensional and complex. Temporal variability in aggregate properties, like total biomass or abundance, is typically lower in communities with higher species diversity (i.e., the diversity–stability relationship [DSR]). At broader spatial extents, regional‐scale aggregate variability is also lower with higher regional diversity (in plant systems) and with lower spatial synchrony. However, focusing exclusively on aggregate properties of communities may overlook potentially destabilizing compositional shifts. It is not yet clear how diversity is related to different components of variability across spatial scales, nor whether regional DSRs emerge across a broad range of organisms and ecosystem types. To test these questions, we compiled a large collection of long‐term metacommunity data spanning a wide range of taxonomic groups (e.g., birds, fish, plants, invertebrates) and ecosystem types (e.g., deserts, forests, oceans). We applied a newly developed quantitative framework for jointly analyzing aggregate and compositional variability across scales. We quantified DSRs for composition and aggregate variability in local communities and metacommunities. At the local scale, more diverse communities were less variable, but this effect was stronger for aggregate than compositional properties. We found no stabilizing effect of γ‐diversity on metacommunity variability, but β‐diversity played a strong role in reducing compositional spatial synchrony, which reduced regional variability. Spatial synchrony differed among taxa, suggesting differences in stabilization by spatial processes. However, metacommunity variability was more strongly driven by local variability than by spatial synchrony. Across a broader range of taxa, our results suggest that high γ‐diversity does not consistently stabilize aggregate properties at regional scales without sufficient spatial β‐diversity to reduce spatial synchrony.

Demographic synthesis for global tree species conservation - Bettina Ohse; Aldo Compagnoni; Caroline E. Farrior; Sean M. McMahon; Roberto Salguero-Gómez; Nadja Rüger; Tiffany M. Knight (Trends in Ecology & Evolution, 2023)

Phenotypic plasticity masks range‐wide genetic differentiation for vegetative but not reproductive traits in a short‐lived plant - Jesus Villellas; Johan Ehrlén; Elizabeth E. Crone; Anna Mária Csergő; Maria B. Garcia; Anna‐Liisa Laine; Deborah A. Roach; Roberto Salguero‐Gómez; Glenda M. Wardle; Dylan Z. Childs; Bret D. Elderd; Alain Finn; et al. (Ecology Letters, 2021)
Genetic differentiation and phenotypic plasticity jointly shape intraspecific trait variation, but their roles differ among traits. In short‐lived plants, reproductive traits may be more genetically determined due to their impact on fitness, whereas vegetative traits may show higher plasticity to buffer short‐term perturbations. Combining a multi‐treatment greenhouse experiment with observational field data throughout the range of a widespread short‐lived herb, Plantago lanceolata , we (1) disentangled genetic and plastic responses of functional traits to a set of environmental drivers and (2) assessed how genetic differentiation and plasticity shape observational trait–environment relationships. Reproductive traits showed distinct genetic differentiation that largely determined observational patterns, but only when correcting traits for differences in biomass. Vegetative traits showed higher plasticity and opposite genetic and plastic responses, masking the genetic component underlying field‐observed trait variation. Our study suggests that genetic differentiation may be inferred from observational data only for the traits most closely related to fitness.

Lagged and dormant season climate better predict plant vital rates than climate during the growing season - Sanne M. Evers; Tiffany M. Knight; David W. Inouye; Tom E. X. Miller; Roberto Salguero‐Gómez; Amy M. Iler; Aldo Compagnoni (Global Change Biology, 2021)
Understanding the effects of climate on the vital rates (e.g., survival, development, reproduction) and dynamics of natural populations is a long‐standing quest in ecology, with ever‐increasing relevance in the face of climate change. However, linking climate drivers to demographic processes requires identifying the appropriate time windows during which climate influences vital rates. Researchers often do not have access to the long‐term data required to test a large number of windows, and are thus forced to make a priori choices. In this study, we first synthesize the literature to assess current a priori choices employed in studies performed on 104 plant species that link climate drivers with demographic responses. Second, we use a sliding‐window approach to investigate which combination of climate drivers and temporal window have the best predictive ability for vital rates of four perennial plant species that each have over a decade of demographic data ( Helianthella quinquenervis , Frasera speciosa , Cylindriopuntia imbricata , and Cryptantha flava ). Our literature review shows that most studies consider time windows in only the year preceding the measurement of the vital rate(s) of interest, and focus on annual or growing season temporal scales. In contrast, our sliding‐window analysis shows that in only four out of 13 vital rates the selected climate drivers have time windows that align with, or are similar to, the growing season. For many vital rates, the best window lagged more than 1 year and up to 4 years before the measurement of the vital rate. Our results demonstrate that for the vital rates of these four species, climate drivers that are lagged or outside of the growing season are the norm. Our study suggests that considering climatic predictors that fall outside of the most recent growing season will improve our understanding of how climate affects population dynamics.

Seismic microzoning map: approaches, results and applications after the 2016–2017 Central Italy seismic sequence - F. Pergalani; A. Pagliaroli; C. Bourdeau; M. Compagnoni; L. Lenti; M. Lualdi; C. Madiai; S. Martino; R. Razzano; C. Varone; V. Verrubbi (Bulletin of Earthquake Engineering, 2020)

Site response analyses for complex geological and morphological conditions: relevant case-histories from 3rd level seismic microzonation in Central Italy - A. Pagliaroli; F. Pergalani; A. Ciancimino; A. Chiaradonna; M. Compagnoni; F. de Silva; S. Foti; S. Giallini; G. Lanzo; F. Lombardi; L. Luzi; L. Macerola; et al. (Bulletin of Earthquake Engineering, 2020)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Microzonation study in the Paganica-San Gregorio area affected by the April 6, 2009 L’Aquila earthquake (central Italy) and implications for the reconstruction - M. Compagnoni; F. Pergalani; P. Boncio (Bulletin of Earthquake Engineering, 2011)